2023
DOI: 10.3390/jcm12041641
|View full text |Cite
|
Sign up to set email alerts
|

Chitotriosidase and Neopterin as Potential Biomarkers for the Evaluation of Complicated Cholecystitis—A Pilot Study

Abstract: Gallstones are a common surgical pathology. Laparoscopic cholecystectomy represents the elective treatment. Complicated cases can increase the rate of conversion, the duration, and the difficulty of the intervention, along with the hospitalization period. A prospective cohort study was conducted on 51 patients with gallstones. Only subjects with normal renal, pancreatic, and hepatic functions were included. The severity of cholecystitis was evaluated by considering the ultrasound examination, intraoperative fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Several studies found CRP to be a good predictive factor for conversion; however, the cut-off values varied widely from 76 mg/L to 220 mg/L [5,[10][11][12][13]. Together with the valuable findings provided by ultrasound and CT exam, specific biomarkers were analyzed for the possible predictive role for the severity of local inflammation, such as the YKL-40 protein level [14], serum level of visfatin [15], procalcitonin [16], human neutrophil lipocalin [17], chitotriosidase, and neopterin [18]. However, their availability in emergencies is limited in many surgical departments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies found CRP to be a good predictive factor for conversion; however, the cut-off values varied widely from 76 mg/L to 220 mg/L [5,[10][11][12][13]. Together with the valuable findings provided by ultrasound and CT exam, specific biomarkers were analyzed for the possible predictive role for the severity of local inflammation, such as the YKL-40 protein level [14], serum level of visfatin [15], procalcitonin [16], human neutrophil lipocalin [17], chitotriosidase, and neopterin [18]. However, their availability in emergencies is limited in many surgical departments.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the systemic inflammatory biomarkers, neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR), were investigated for their predictive value in many inflammatory and septic conditions [18][19][20][21][22], such as septic shock, diabetic foot ulcer, acute appendicitis, and spontaneous bacterial peritonitis. They are cheap and inexpensive biomarkers, easy to calculate based on the complete blood count (CBC).…”
Section: Introductionmentioning
confidence: 99%
“…For bacterial diseases, Np was proposed to predict complicated cholecystitis. A 3.34 times higher risk of complications was reported in subjects with Np levels that exceeded the cut-off limit (>14.69 nmol/L) [85]. Np is also a valuable biomarker for the diagnosis of acute appendicitis but was not able to predict the severity of the disease [86].…”
Section: Neopterin and Bacterial And Viral Diseasesmentioning
confidence: 98%